THE PHARAOH: LIFE AT COURT AND ON CAMPAIGN - Shaw, Garry J.; Sleeper, Barbara (London : Thames & Hudson, 2012)
The first book to convey the full experience of what it was actually like to be pharaoh one of the most powerful rulers of the ancient world, Garry Shaw covers, through eight themed chapters, all aspects of the realities of pharaohs life, from mornings waking in the palace to evenings spent banqueting, with all his duties and activities in between.
Includes bibliographical references and index.
Keywords: Anderson, Mary Ann, -- 1946-2011; Pharoahs; Egypt -- History -- To 332 B.C.